Digoxin vs. beta-blocker therapy in atrial fibrillation: analysis from the ESC-EHRA EORP Atrial Fibrillation General Long-Term (AFGen LT) Registry. (14th October 2021) - Ding, W.Y; Proietti, M; Boriani, G; Marin, F; Blomstrom-Lundqvist, C; Fauchier, L; Potpara, T.S; Lip, G.Y.H
Abstract: Background: There is a long-standing and unresolved controversy over the effects of digoxin on mortality. Furthermore, there is scarce evidence comparing the use of digoxin to beta-blocker in the general population with atrial fibrillation (AF). In this study, we aimed to evaluate the effects of digoxin over beta-blocker therapy among patients with AF. Methods: Patients from the EORP-AF General Long-Term Registry with AF who were treated with either digoxin or beta-blocker were included. All patients were over 18 years old and had documented evidence of AF within 12 months prior to enrolment. The outcomes of interest were all-cause mortality, cardiovascular (CV) mortality, non-CV mortality and number of patients with unplanned hospitalisation (total and AF-related). These were recorded until the last known follow-up available. Results: Of 6377 patients, 549 (8.6%) and 5828 (91.4%) were treated with digoxin and beta-blockers, respectively. Patients in the digoxin group were older (73 vs. 71 years, p<0.001) with reduced renal function (eGFR 65.4 vs. 68.7 mL/min/1.73m 2, p=0.002), and had (in general) greater burden of comorbidities in terms of chronic kidney disease, chronic obstructive pulmonary disease, heart failure, hypertension and peripheral artery disease. Nonetheless, the use of anticoagulation therapy was comparable between both groups (p=0.112). Over 24 months follow-up, there were 550 (8.6%) all-cause mortality and 1304 (23.6%) patients with unplanned emergency hospitalisation. Digoxin use was associated with increased all-cause mortality (hazard ratio [HR] 1.90 [95% CI, 1.48–2.44]), both from CV and non-CV causes (CV: HR 2.21 [95% CI, 1.49–3.26]); non-CV: HR 1.70 [95% CI, 1.04–2.79]). There was no statistical difference in terms of unplanned emergency hospitalisation (HR 0.99 [95% CI, 0.80–1.21]) and AF-related hospitalisation (HR 0.78 [95% CI, 0.58–1.06]) between both groups. Using multivariable cox regression analysis, digoxin compared to beta-blocker therapy was independently linked to increased all-cause mortality (HR 1.52 [95% CI, 1.11–2.09]) and CV mortality (HR 1.82 [95% CI, 1.11–2.97]), but was not related to non-CV mortality (HR 1.31 [95% CI, 0.71–2.41]), emergency hospitalisation (HR 0.91 [95% CI, 0.71–1.16]) or AF-related hospitalisation (HR 0.88 [95% CI, 0.62–1.24]), after adjustment for known risk factors. Conclusion: We demonstrated that the use of digoxin was independently associated with excess all-cause mortality, driven by CV death, but was non-inferior to beta-blocker in terms of preventing unplanned emergency or AF-related hospitalisation, after accounting for important risk factors. Funding Acknowledgement: Type of funding sources: None.